2023
DOI: 10.3389/fphar.2023.1169812
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of Lycium shawii on human melanocyte proliferation, migration, and melanogenesis: In vitro and in silico studies

Abstract: There is no first-line treatment for vitiligo, a skin disease characterized by a lack of melanin produced by the melanocytes, resulting in an urgent demand for new therapeutic drugs capable of stimulating melanocyte functions, including melanogenesis. In this study, traditional medicinal plant extracts were tested for cultured human melanocyte proliferation, migration, and melanogenesis using MTT, scratch wound-healing assays, transmission electron microscopy, immunofluorescence staining, and Western blot tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Notably, the culture of HEMn-LP cells in PMA-free HMGS (HMGS-2 [116]) causes cells to synthesize lower melanin and remain bipolar with low dendrite number [117,118] and was employed in some of the previous studies that reported on compounds that stimulated melanogenesis in primary human melanocytes cultured with HMGS-2 supplement [119][120][121]. The use of HMGS-2 might have been a better choice to study the isolated effects of CYC in promoting pigmentation; however, previous reports have utilized HMGS in their experiments with compounds that stimulated melanogenesis [122,123]; hence, the use of HMGS is acceptable. Additionally, in our earlier studies that reported on stimulators of melanogenesis, we have continued to use HMGS medium only [39,75].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the culture of HEMn-LP cells in PMA-free HMGS (HMGS-2 [116]) causes cells to synthesize lower melanin and remain bipolar with low dendrite number [117,118] and was employed in some of the previous studies that reported on compounds that stimulated melanogenesis in primary human melanocytes cultured with HMGS-2 supplement [119][120][121]. The use of HMGS-2 might have been a better choice to study the isolated effects of CYC in promoting pigmentation; however, previous reports have utilized HMGS in their experiments with compounds that stimulated melanogenesis [122,123]; hence, the use of HMGS is acceptable. Additionally, in our earlier studies that reported on stimulators of melanogenesis, we have continued to use HMGS medium only [39,75].…”
Section: Discussionmentioning
confidence: 99%
“…Melanin is a pigment produced in plants, microorganisms, and animals ( Alghamdi et al, 2023 ). In skin, its role is to protect the skin from ultraviolet (UV) radiation damage ( Shen et al, 2019 ; Nazir et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%